Desenvolvimento de competências gerenciais de diretores de Escolas Públicas Estaduais de João Pessoa/PB - Galvão, Verônica Bezerra de Araújo (2010)
This research aims to analyze the process of development of managerial skills put into action by directors of public schools. To explore the central theme of the study, it was organized a theoretical basis for addressing public education in context of human development policy; the meaning of work under the sign of uncertainty; the activity and managerial learning and concept of competencies. The descriptive research departed from the study of Galvão and Cavalcanti (2009), which mapped 25 managerial competencies required and mobilized by school principals, categorizing them into three dimensions: technical, social and behavioral. In order to collect data, a questionnaire was applied, whereby the school principals were able to evaluate two aspects: the importance of skills and the degree of influence of formal education, professional experience and social experience in its development. The socio-demographic profile of the respondents was also part of the investigation. The sample involved 58 basic education schools of the state, located in the city of Joao Pessoa. In the first stage of the study, a factorial analysis of the skills was made, obtaining a set of 04 skills in the technical dimension, 02 in the social dimension and 04 in the behavioral dimension. All of them were given labels based on attributes gathered by each factor. The assessment of significance showed that the skills that were most enforced by the directors were: "to promote family-school integration‖, ―discipline the team‖, and ―learning to learn‖. Even though there were different degrees of importance, it was noticed that the striking feature of the skills is their relationship of complementarity and the possibility to be mobilized in the face of events that underlie managerial action. Concerning the influence, in all cases, formal education had lower contribution. However, the lack of formal education seemed offset by the experience linked to social or professional context, which was capable of enhance "subjects" related to the management of uncertainty. For an upcoming future, it is suggested an investigation of the structure of skills training for school managers, duo to the responsibility assigned to management schools, especially the public universities. The general results point to the complexity surrounding the school and capture the urgency that needs to be dealt with the construction of public policies for the strengthening of managerial action. Regarding, overall, to articulate learning and experience in stage of skills training. It is believed that this research can contribute to a continuity and increase of the studies and scientific debates, in time to facilitate a movement of critical thoughts in order to school keep advancing and acquiring more quality.